Current situation and future prospects of Echinococcus granulosus vaccine candidates: A systematic review. Issue 3 (20th August 2020) - Anvari, Davood; Rezaei, Fatemeh; Ashouri, Alireza; Rezaei, Saeed; Majidiani, Hamidreza; Pagheh, Abdol Sattar; Rezaei, Fatemeh; Shariatzadeh, Seyyed Ali; Fotovati, Amir; Siyadatpanah, Abolghasem; Gholami, Shirzad; Ahmadpour, Ehsan
Abstract: Cystic echinococcosis is a worldwide zoonotic disease, represents a threat for livestock and humans, manifests as a quiescent, subclinical and chronic hydatid cyst infection. The disease imposes high expenditures and economic losses in medical and veterinary. Prophylactic vaccination would be one of the effective preventive health care against echinococcosis. During the last decades, many studies have characterized the protective antigens of Echinococcus granulosus and their role in immunization of various animal host species. Herein, we aimed to systematically evaluate and represent the best antigens as possible vaccine candidates for cystic echinococcosis. Data were systematically searched from five databases including ProQuest, PubMed, Scopus, ScienceDirect and Web of Science, up to 1 February 2020. Two reviewers independently screened and assessed data extraction and quality assessment. A total of 47 articles were eligible for inclusion criteria in the current study. The most common antigens used for vaccination against E. granulosus were EG95 and antigen B. Freund's adjuvant and Quil A have been predominantly utilized. In addition, regarding the antigen delivery, animal models, measurement of immune responses and reduction in hydatid cyst have been discussed in the text. The data demonstrated that DNA vaccines with antigen B and recombinant protein vaccines based on EG95 antigen have the best results and elicited protective immune responses.